Guru Kelas Sebagai Pelaksana Layanan Bimbingan dan Konseling di Sekolah Dasar - Eka Prasetia; Ainun Heiriyah (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine the Role of Class VI Teachers as Guidance and Counseling Service Implementers at State Elementary School 4 Sungai Andai Banjarmasin. The approach in this study uses a qualitative approach with a phenomenological research design. The method used in this study in collecting data is to use interview and documentation techniques. In this study, it was found that the sixth-grade teacher at Sungai Andai 4 Elementary School understood and understood his role as a a guidance and counseling teacher. But Grade VI teachers experience several obstacles in providing guidance and counseling services, namely facilities and infrastructure, academic and practical implementation of counseling guidance because they are not pure S1 Guidance and Counseling graduates. Efforts made by class VI teachers at Sungai Andai Elementary School to support the implementation of guidance and counseling services are by reading books and articles related to guidance and counseling services, in addition to the lack of knowledge in Guidance and Counseling management for Class VI teachers at Sungai Andai 4 Elementary School Banjarmasin. resulting in a lack of documents used in the BK administration, only one document that they made, namely a book listing student problem and the solutions provided by them.